Reflexiones teóricas del derecho público y justicia - De Los Ríos Castiblanco, Juan Carlos (Corporación Universitaria Americana, 2018)
The text "Theoretical Reflections on Public Law and Justice" is the result of research within the framework of the methodological strategy of evaluation of actions, strategies and pedagogical contents of the subjects corresponding to the area of public law in the training of lawyers. In order to evaluate and identify the topics that present difficulties in the apprehension of knowledge in the area of public law, it was decided to know the common pedagogical actions and strategies in the teaching of public law, characterizing the successful models and weaknesses of learning. Subsequently, the thematic axes that show difficulties in learning were identified. And in the third stage, with this research book, we elaborated contents of thematic axes of difficult learning with alternative methods of reinforcement as some of the products of the project.